2017
DOI: 10.1136/bmjopen-2016-015236
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the health economic burden of patients with tuberous sclerosis complex (TSC) with epilepsy: a retrospective cohort study in the UK Clinical Practice Research Datalink (CPRD)

Abstract: IntroductionEpilepsy is highly prevalent in tuberous sclerosis complex (TSC), a multi-system genetic disorder. The clinical and economic burden of this condition is expected to be substantial due to treatment challenges, debilitating co-morbidities and the relationship between TSC-related manifestations. This study estimated healthcare resource utilisation (HCRU) and costs for patients with TSC with epilepsy (TSC+E) in the UK.MethodsPatients with TSC+E in the Clinical Practice Research Datalink (CPRD) linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(77 citation statements)
references
References 32 publications
9
64
4
Order By: Relevance
“…These different manifestations are grouped under the term "TSCassociated neuropsychiatric disorders" (TAND). Data from the TOSCA registry [21] revealed that 54.9% of persons with TSC had some level of intellectual disability (50 to 65% in prior studies [1,23,[35][36][37]), with good agreement present between caregiver-reported and psychometric Table 1 Prevalence of common clinical manifestations in TSC patients (Continued)…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 93%
See 3 more Smart Citations
“…These different manifestations are grouped under the term "TSCassociated neuropsychiatric disorders" (TAND). Data from the TOSCA registry [21] revealed that 54.9% of persons with TSC had some level of intellectual disability (50 to 65% in prior studies [1,23,[35][36][37]), with good agreement present between caregiver-reported and psychometric Table 1 Prevalence of common clinical manifestations in TSC patients (Continued)…”
Section: Neuropsychiatric Manifestationsmentioning
confidence: 93%
“…Subependymal giant cell astrocytomas (SEGAs) were found in 24.4% of the TOSCA population. SEGA can obstruct the intraventricular space and lead to noncommunicating hydrocephalus requiring surgery (22.4% of those [20][21][22][23][24][25] The prevalence rate (32.9%, 35.9%) of pharmacoresistant epilepsy is similar to general population with focal epilepsy [26,27]. A mutation in the TSC2 gene is a risk factor for infantile spasms (47.3% vs. 23% with TSC1 in TOSCA) as well as an earlier manifestation of epilepsy, a higher seizure frequency, and pharmacological refractoriness [28].…”
Section: Neurological Manifestationsmentioning
confidence: 97%
See 2 more Smart Citations
“…As such, the care of TSC is associated with increased health care resource utilization as well as costs and the condition itself has profound impacts on quality of life. [12][13][14][15] Given the recent development of a comprehensive TSC clinic at our center, we aimed to better understand the care delivered to children with TSC before being seen in our TSC clinic to determine which gaps in surveillance of TSC care existed by examining whether the 2012 Tuberous Sclerosis Complex Consensus Recommendations were being followed. Of note, a revision to TSC guidelines is anticipated in the near future.…”
Section: Discussionmentioning
confidence: 99%